2020
DOI: 10.1136/bmjopen-2019-035192
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the quality of primary healthcare for diabetes in China: multivariate analysis using the China Health and Retirement Longitudinal Study (CHARLS) Database

Abstract: ObjectiveTo assess the quality of primary healthcare (PHC) for patients with diabetes in China from 2011 to 2015.SettingThis study analysed data on 1006, 1472 and 1771 participants with diabetes who were surveyed in 2011, 2013 and 2015, respectively, in the China Health and Retirement Longitudinal Study, a nationally representative survey conducted in 29 provinces of China.Outcome measuresThe study measured the proportions of patients with diabetes who received diabetes-related health education, examinations a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 44 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…This may be one of the causes for the suboptimal performance in key indicators (e.g., retinopathy, foot, peripheral neuropathy monitoring). Health counseling indicators in our study, such as diet counseling (79.5%) and exercise counseling (76.9%) were performed better than another national survey in China (diet 65.0%, exercise 49.0%) [ 11 ], the main reason might be that the general practice in CHSC in Beijing were better developed and can provide relatively high-quality services, compared with other regions in China [ 35 ]. There was still room for improvement, especially in medication safety (48.3%) and emergency help counseling (42.5%).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This may be one of the causes for the suboptimal performance in key indicators (e.g., retinopathy, foot, peripheral neuropathy monitoring). Health counseling indicators in our study, such as diet counseling (79.5%) and exercise counseling (76.9%) were performed better than another national survey in China (diet 65.0%, exercise 49.0%) [ 11 ], the main reason might be that the general practice in CHSC in Beijing were better developed and can provide relatively high-quality services, compared with other regions in China [ 35 ]. There was still room for improvement, especially in medication safety (48.3%) and emergency help counseling (42.5%).…”
Section: Discussionmentioning
confidence: 71%
“…And among patients treated, 49.4% had glycosylated hemoglobin (HbA1c) controlled [ 10 ]. Another national study reported that during 2011–2015, the recurrent hospital admission rate among people with diabetes steeply increased from 18.87% to 28.45% [ 11 ]. Health information technology systems for diabetes care are essential for continuity and coordination [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the past ten years of health care reform, China has been working hard to improve the primary health care system, and the government has included diabetes in the national basic public health service projects, including self-management education ( 27 ). However, between 2011 and 2015, the rates of patients with diabetes who received health education showed a decreasing trend ( 28 ). Generally, the quality characteristics of primary health care in China were poor.…”
Section: Discussionmentioning
confidence: 99%
“… 9 Furthermore, a nationally representative study of the quality of PHC for diabetes in China showed that diabetes-related hospitalizations have increased from about 4% in 2011 to 6% in 2013, while recurrent hospitalizations among individuals with diabetes increased from almost 19% in 2011 to 28% in 2015. 11 As hospitalizations serve as a proxy outcome indicator for the quality of primary diabetes care, these findings highlight the urgent need to improve the level of care delivered by primary care practitioners in China.…”
Section: Introductionmentioning
confidence: 97%